Melphalan plus prednisolone in the treatment of multiple myeloma - Begum, M; Akther, A; Khan, KH; Kaiser, MS; Rahman, MJ; Alam, MN (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):93-97 The abstract of this article is available on the PubMed website